Why Programmers Should Curb Their Enthusiasm, and Thinking about Computational Thinking. - Bugayenko, Yegor; Guzdial, Mark (Communications of the ACM, 2019)
The authors discuss the issues of overenthusiastic programmers and computational thinking. They mention programmers who haven't learned to microtask and want to completely overhaul a project's architecture, the question of human-computer interfaces, and programming within a domain.